EFEKTIVITAS PENDIDIKAN KESEHATAN MAGIC SPINNING WHELL TERHADAP PENGETAHUAN PERSONAL HYGIENE REMAJA PUTRI SMPN 1 SERIRIT: EFEKTIVITAS PENDIDIKAN KESEHATAN MAGIC SPINNING WHELL TERHADAP PENGETAHUAN PERSONAL HYGIENE REMAJA PUTRI SMPN 1 SERIRIT - Asmari, Putu Juli; Dewi, Komang Ayu Purnama; Darmayanti, Putu Ayu Ratna (STIKES ADVAITA MEDIKA TABANAN, 2024)
Maintaining the correct and adequate application of personal hygiene by teenagers can prevent infections and co-morbidities. The provision of health knowledge needs to be given through a media that is easy to understand and interesting, hence that teenagers are motivated to know, understand and accept the information given. One example is by using a colorful game media namely the magic spinning wheel. The purpose of this study was to identify the effectiveness of health education through the media of a magic spinning wheel on the personal hygiene knowledge of teenage girls at Junior High School 1 Seririt. This study employed a quantitative research design with the Pre-Experimental method through the One Group Pre-Test and Post-Test design. The sample recruited in this study was 89 teenage girls through probability sampling and simple random sampling. The data were analyzed through the Non-Parametric Wilcoxon Signed Rank Test. Results of the Wilcoxon Signed Rank Test had a p-value of 0.000. The treatment in the form of health education through the media of a magic spinning wheel was proven to be effective on the personal hygiene knowledge of teenage girls at Junior High School 1 Seririt. Conclusion it is suggested that health workers and teachers could use the magic spinning wheel media as one of the health education methods for teenage girls at school, hence it would be more interesting and could foster curiosity among teenage girls about health information.